The Living Qur’an: Pembacaan Surah An- Nasr Sebelum Belajar (Studi Kasus di SDIT Mujahidul Amin) - Niki Lisda (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
There are numerous phenomena practiced by Muslims to enliven and incorporate the Qur’an into their daily lives. The recitation of Surah An-Nasr is not only conducted at SDIT Mujahidul Amin but is also practiced and adopted by several Islamic boarding schools in Palangka Raya. This research was carried out using qualitative methods because the data produced are in the form of words and actions. In collecting data, the instruments used were interviews and observations conducted at SDIT Mujahidul Amin Palangka Raya. Subsequently, the gathered data were analyzed to arrive at clearly described conclusions. The findings of this study indicate that the practice of reading Surah An-Nasr before the start of lessons by the students of SDIT Mujahidul Amin Palangka Raya represents a living Qur’an among the student community. This recitation of Surah An-Nasr is performed every morning after the Dhuha prayer, followed by reading Surah An-Nasr three times and then continuing with a study prayer, a practice that is carried out from grades 1 to 6. Keywords: Living Qur’an; Surah An-Nashr; Learning.